OC-054 Impact of a fermentable carbohydrate restricted diet on luminal microbiota, fermentation, symptoms and nutrient intake in patients with irritable bowel syndrome: a randomised controlled trial. (28th May 2012) - Staudacher, H; Lomer, M C; Anderson, J L; Barrett, J S; Muir, J G; Irving, P M; Whelan, K
Abstract : Introduction: Retrospective studies suggest that dietary restriction of fermentable carbohydrates (Fermentable Oligosaccharides, Disaccharides, Monosaccharides and Polyols, FODMAPs) improves irritable bowel syndrome (IBS) symptoms. Prebiotic fructo-oligosaccharides and galacto-oligosaccharides stimulate colonic bifidobacteria, however the effect of a fermentable carbohydrate restricted diet on the gut microbiota has never been examined. The aim of this randomised controlled trial was to investigate the impact of a fermentable carbohydrate restricted diet on luminal microbiota, fermentation and symptoms in IBS. Methods: Adult patients with IBS were recruited from gastroenterology outpatient clinics. Eligible patients were randomised to the intervention diet or their habitual diet for 4 weeks. A fresh stool sample was collected and analysed for the major bacterial groups using fluorescent in situ hybridisation, short chain fatty acid (SCFA) concentration was analysed using gas liquid chromatography and pH was recorded. The incidence and severity of GI symptoms and stool output were recorded and dietary intake was assessed using food diaries. All outcome measures were recorded at baseline and 4 weeks. Continuous data were compared using an independent samples t-test and categorical data were compared using the χ 2 test. Results: Of 41 patients randomised, six withdrew (five protocol violations, one lost to follow-up). In the intention-to-treat analysis, more patients in the intervention group reported adequate control of symptoms (68%) compared with controls (23%) (p=0.003). However, there were strikingly lower concentrations (7.4 vs 8.2 log10 cells/g, p=0.001) and proportions (1.2% vs 5.5%, p=0.002) of bifidobacteria in the intervention group compared with controls at follow-up. This was not associated with any change in luminal markers of fermentation. There were no differences in energy, protein or fat intake at 4 weeks between groups but total carbohydrate intake was lower in the intervention group. Conclusion: This is the first randomised controlled trial investigating the effect of a fermentable carbohydrate restricted diet, demonstrating significant improvements in symptoms but a dramatic reduction in luminal bifidobacteria, a species that have an important role in colonic health. Significant questions remain; is the shift in bifidobacteria permanent, how might it be prevented and what is the impact of reintroduction of fermentable carbohydrates on the microbiota? Competing interests: None declared.